KAJIAN POPULASI ALAMI BUNGA BANGKAI (Amorphophallus titanum (Becc.) Becc.): STUDI KASUS DI KAWASAN HUTAN BENGKULU - Hidayat, Syamsul; Yuzammi, Yuzammi (Buletin Kebun Raya, 2008)
Amorphophallus titanum (Becc.) Becc. is a species of Aroid family that produces an attractive large-inflorescence. It is well known as one of the largest inflorescence producing species in the world. The plant is endemic to Sumatera Island and has long been considered as a threatened species. However, in 2002, the IUCN removed it from the Red List of Threatened Plants chiefly because of inadequate data regarding the existence of the species in nature. This present study was carried out in Bengkulu as a case study in attempt to provide information concerning the natural population and the potential threats towards the existence of A. titanum in Sumatera. The results of the observation are disccused thoroughly in this paper.